Attitudes towards COVID-19 vaccination, vaccine hesitancy and vaccine literacy among unvaccinated young adults: - Gulay YILMAZEL; Emre KELES; Ayse CALMAZ; Burcu DAYSAL GULER (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundHerd immunity is necessary to control the coronavirus disease 2019 (COVID-19) pandemic. Unfortunately, attaining herd immunity is a significant challenge for current healthcare systems worldwide, and the prevalence of hesitancy toward COVID-19 remains high. The aim of this study was to determine pandemic vaccine hesitancy, attitudes towards COVID-19 vaccine and COVID-19 vaccine literacy level in vaccination period among unvaccinated young adults. MethodsThis cross-sectional study was carried out in the province of Çorum in Turkey. Unvaccinated young adults (n=860) between the ages of 18-30 studying medicine and non-medical sciences of a university were included in the study. Socio-demographic form, and the scales on Pandemic Vaccine Hesitancy, Attitudes towards the COVID-19 vaccine, COVID-19 vaccine literacy were used to collect the research data. The data were analyzed using percentages, median values, regression analysis. Results The study was completed with 860 participants. In the group, 73.8% were 18-24 years 67.7% were women and 68.0% were infected with the virus. The median scores from the pandemic vaccine hesitancy scale, vaccine literacy and vaccine attitudes were 33, 27 and 30 respectively. Use of social media in daily, vaccine literacy and COVID-19 vaccine attitude were effective factors on pandemic vaccine hesitancy (p<0.05). Negative attitude to vaccines was the most influenced risk factor of vaccine hesitancy (Beta = 0.248). ConclusionPandemic vaccine hesitancy is a phenomenon that coincides with low vaccine literacy and negative attitudes towards vaccines. COVID-19 vaccination information campaigns should promote group strategies, focusing on emphasising the safety of the vaccine and offer reassurance.